Sun-curing and harvest maturity impacts concentration and protein-binding capacity of condensed tannins in sericea lespedeza (lespedeza cuneata) - Eckerle, G.J.; Pacheco, L.A.; Olson, K. C.; Jaeger, John R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Sericea lespedeza (Lespedeza cuneata) is a noxious weed that infests approximately 600,000 acres of native tallgrass range in Kansas. Intake of sericea lespedeza by grazing livestock is poor, presumably as a result of the plant’s tannins. Condensed tannins reduce protein digestion by ruminants and may also decrease plant palatability.
Beef Cattle Research, 2011 is known as Cattlemen’s Day, 2011
Keywords: Beef; Protein; Tannins; Sericea lespedeza